2022
DOI: 10.1177/10944281221075361
|View full text |Cite
|
Sign up to set email alerts
|

Attitude Toward the Color Blue: An Ideal Marker Variable

Abstract: Researchers often turn to post hoc statistical techniques to identify common method variance (CMV) in same source data and one viable option is to use a marker variable. The choice of marker variable is important, yet these variables are difficult to find, primarily because they must be theoretically unrelated to study variables but measured in the same way (e.g., perceptual; on a Likert scale). This manuscript uses scale development best practices to create a marker variable—attitude toward the color blue—tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(20 citation statements)
references
References 75 publications
0
20
0
Order By: Relevance
“…We used both the marker variable technique and multicollinearity test. For the marker variable technique, four items of attitude towards the color blue scale which had no theoretical link to other constructs in the study were included in the surveys (Time 1) (Miller and Simmering, 2022). The CMV threat was not an issue, as discarding the marker variable had no influence on the significance of the correlations (Tables 1 and 2 of the Supplementary file) (Lindell and Whitney, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…We used both the marker variable technique and multicollinearity test. For the marker variable technique, four items of attitude towards the color blue scale which had no theoretical link to other constructs in the study were included in the surveys (Time 1) (Miller and Simmering, 2022). The CMV threat was not an issue, as discarding the marker variable had no influence on the significance of the correlations (Tables 1 and 2 of the Supplementary file) (Lindell and Whitney, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…Statistically, the researcher uses ATCB [87] as a marker variable in Lindell and Whitney's [91] partial correlation techniques to account for the potential CMV. As seen in Table 2, there is no CMV bias since the correlations between ATCB and other substantive variables are the lowest, not significant, and there is no change in correlation between the substantive variables either in value or significant before and after controlling by ATCB.…”
Section: Common Methods Bias Assessmentmentioning
confidence: 99%
“…Attitude Toward the Color Blue (ATCB) measure: The researcher resorted to using the seven-item scale developed and recommended by Miller and Simmering [87] as an important statistical technique to identify the Common Method Variance (CMV) through inserting it as a marker variable into the questionnaire. A sample item in this scale is "I like the color blue", and "The color blue is wonderful".…”
Section: Variables Measurement and Questionnaire Designmentioning
confidence: 99%
“…We further found that the AVE (average variance extracted) scores were greater than the square of the bivariate correlations, establishing discriminant validity ( Fornell and Larcker, 1981 ). Apart from collecting the data at two time periods, we used an established marker variable (i.e., attitude toward blue color) to minimize common method variance ( Miller and Simmering, 2022 ).…”
Section: Methodsmentioning
confidence: 99%